Profile of amino acids production from microalgae Nannochloropsis sp. biomass using subcritical water technology - Zainan, Nur Hidayah Binti; Harun, Razif; Kamal, Siti Mazlina Mustapa; Sapardi, Mohd Azan Mohammed (Universitas Gadjah Mada, 2022)
The amino acids from microalgae could be used as a substitute for food and feed supplements in the future. This study investigates the production of amino acids from microalgae Nannochloropsis sp. biomass using subcritical water technology approaches. The yield and composition of amino acids produced from subcritical water of microalgae Nannochloropsis sp. were evaluated at different temperatures (160-350 °C), time (3-30 min), and biomass loadings (1- 15% w/v). Overall results showed that the highest yield of total amino acids (1531.98 mg/100 g algae) was obtained at subcritical water operating conditions of 280 °C, 15 min reaction time, and 1% biomass loading. The studied operating conditions produced a higher yield of non-essential amino acids compared to essential amino acids. The study demonstrated that each of the individual amino acids investigated produced the highest at different ranges of subcritical water conditions. Thus, the obtained profile of the individual amino acid showed that careful management of operating parameters (temperature, time, and biomass loading) is crucial for identifying the amino acids of interest via subcritical water technology.